ESTIMASI PARAMETER TEGAKAN HUTAN RAWA GAMBUT MENGGUNAKAN DATA SPEKTRAL CITRA LANDSAT 7 ETM+ DI KALIMANTAN TENGAH Estimation of Forest Stand Parameters using Spectral Data Landsat 7 ETM+ In Central Kalimantan: Raden Mas Sukarna, Cakra Birawa, Misrita - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTEstimation of forest stand parameters such as stand density, dominancy and frequency in a large areausing remotely sensed data has considerable significance for sustainable management and utility ofnatural resources. In practice, selecting suitable image data for such purposes remains difficult due to apoor understanding of forest stand parameters and remote-sensing spectral response relationships,particularly in Peat Swamp Forest (PSF) regions. This paper explores relationships between foreststand parameters and Landsat 7 Enhanced Thematic Mapper (ETM+) spectral responses throughForest Canopy Density (FCD) analyses of peat swamp forest in Central Kalimantan Indonesia. SevenETM bands and many biophysical indices are examined through integration of spectral responses andfield vegetation inventory data. Pearson’s correlation coefficients are used to interpret relationshipsbetween forest stand parameters and ETM data through FCD. This study concludes that FCD andstand density, stand dominancy and species frequency are most strongly correlated, and we canestimate standing stock of forest accurately.Keywords: forest canopy density; stand density, dominancy, frequency, peat swamp forest